WHY DO VIETNAMESE FIRMS HOLD CASH? - Nguyễn Thanh Hồng Ân; Hoàng Mai Phương (Tạp chí Khoa học Đại học Đà Lạt)
This research aims at exploring the current state and the reasons for holding cash of Vietnamese firms. Using a dataset of 199 companies listed on the Ho Chi Minh City Stock Exchange in the period from 2011 to 2018, statistical analyses indicate that the median level of cash holding by net assets of Vietnamese firms is about 5.9%, which is lower than firms in many countries in the region. High levels of cash holding only appear among small firms. In addition, the cash holding ratios of firms in all four size quantiles have shrunk since 2016, especially for firms in the smallest size quantile. Regression results show that Vietnamese firms tend to hoard cash when business conditions improve, when they have low growth opportunities, or when business risks increase. On the other hand, Vietnamese firms tend to reduce holding cash when other internal sources of cash substitutes are in abundance or when external fund accessibility improves. These characteristics support the trade-off theory of cash holding, meaning that Vietnamese firms hold cash mainly for transactional and precautionary purposes. Additional analyses show that the rate of adjustment of cash holding toward the target level is about 30% a year. Taken together, the results confirm the hypothesis that Vietnamese firms hold cash for transactional and precautionary purposes, and they constantly reconsider the benefits and costs of adjusting cash holding ratios to the target levels. The research results have two main implications. Firstly, the fact that firms with low growth opportunities have higher cash holding ratios indicates that these firms’ board of directors may have been inefficient in monitoring and disciplining the behavior of firms’ executives toward shareholder interests. Secondly, the fact that Vietnamese firms have low and dwindling cash holdings in recent years and use their cash stock mainly for transactional and precautionary purposes may be a sign of internal resource deficiency. Given that internal resources are vital to investments in research and development, which in turn contribute to firms’ future growth and competitiveness, the current low level cash holding is a bad sign for the future growth as well as the long-term competitiveness of Vietnamese firms.